Development of a Water-Soluble Nanomicellar Formulation Loaded with Trans-Resveratrol Using Polyethylene Glycol Monostearate for the Treatment of Intracerebral Hemorrhage - Kengo Banshoya; Aoi Machida; Saki Kawamura; Tetsuhiro Yamada; Riko Okada; Yui Kawamoto; Hikaru Kimura; Sachi Shibata; Yuhzo Hieda; Yoshiharu Kaneo; Tetsuro Tanaka; Masatoshi Ohnishi (MDPI AG, 2024)
Background/Objectives: Trans-resveratrol (Res) has been reported to possess many biological activities, including neuroprotective effects, owing to its anti-inflammatory and antioxidant properties. However, Res has very low water solubility, which limits its therapeutic application. In this work, we formulated water-soluble micellar formulations incorporating Res using polyethylene glycol monostearate (stPEG). Methods: These formulations (stPEG/Res) were developed using five types of stPEG containing 10, 25, 40, 55 and 140 PEG repeat units. The formulations were characterized for Res content, water solubility, particle size, zeta potential, precipitation, biodistribution, and efficacy against neuronal and motor dysfunction in intracerebral hemorrhage (ICH). Results: Intravenous administration of stPEG40/Res, which demonstrated particle size, water solubility, and biodistribution properties suitable for intravenous administration, suppressed neurological and motor dysfunction following in a collagenase-induced ICH mouse model. These effects were inhibited by zinc protoporphyrin-9, an inhibitor of the antioxidant enzyme heme oxygenase-1, suggesting that Res contributes to antioxidant enzyme expression and anti-inflammatory activity. Conclusions: The stPEG/Res micellar formulation developed in this study may offer a promising therapeutic approach for ICH treatment.